The Role of Soft Skills for Innovation at the SME Sector in Malaysia - Md Atiqur Rahman Sarker; Tariq Salameh Albluwi (Journal of Management Research, 2024)
Small and Medium Enterprise (SME) is booming in Malaysia and this sector also has many challenges. SME becomes sustainable and successful venture when the innovation and creativity are considered largely in doing the business. Soft skills are essential in this regard since it requires human relations in every business transaction. The objective of this research is to explore the role of various soft skills and their relations with innovation in the SME sector in Malaysia. For the methodology, the research used the inductive approach by performing six In-depth Interviews following Yin (2003). The results of this research have identified that communication, teamwork, leadership, critical thinking, positive attitudes, flexibility, and adaptability are the most used soft skills that help the entrepreneurs to be innovative and being successful in SME sectors in Malaysia. The results of this study will help the entrepreneurs in Malaysia to understand the essential soft skills for them to push towards innovative results. This one of the few qualitative research that comprehensively explores the relation between soft skills and innovation in Malaysia.